2021
DOI: 10.4317/jced.58723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active application of self-etching ceramic primer on the long-term bond strength of different dental CAD/CAM materials

Abstract: Background The objective of this in vitro study was to evaluate the effect of the active application of self-etching ceramic primer (ME&P) on the bond strength of different dental CAD/CAM materials (Lithium Disilicate ceramic (LD), Leucite ceramic (LE), Zirconia reinforced lithium silicate ceramic (ZLS), and Hybrid ceramic (HC)) with thermocycling aging. Material and Methods The samples were randomly divided into 16 groups (n = 20). Dual resin cement cylinders were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Therefore, further studies considering aging protocols are strongly advocated to investigate the bond strength in long-term behavior. 34 35 36 In addition, as an in vitro study, this research did not consider all the factors present in the oral medium, such as fatigue 37 and pH variation. Clinical studies are also suggested to corroborate or contradict the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies considering aging protocols are strongly advocated to investigate the bond strength in long-term behavior. 34 35 36 In addition, as an in vitro study, this research did not consider all the factors present in the oral medium, such as fatigue 37 and pH variation. Clinical studies are also suggested to corroborate or contradict the present findings.…”
Section: Discussionmentioning
confidence: 99%